1971
DOI: 10.2466/pms.1971.33.3f.1123
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Learning with Rhythmic and Nonrhythmic Background Music

Abstract: Groups of rats learned a discrimination problem in a four-choice apparatus while exposed to one of six auditory stimulus conditions. The stimuli were: a selection of Mozart, an amelodic version of this piece, a selection of Schoenberg, an amelodic version of this piece, white noise, and quiet. None of the groups acquired the discrimination more quickly than quiet controls. Ss exposed to the Schoenberg music, the amelodic version of it, and to white noise performed more poorly than the controls. Presence of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Our concern was whether a music environment is always good? Most of the reports in the literatures have focused on the beneficial effect of music 1 20 , but an early report also suggested that stimulation with non-rhythmic Schoenberg music (Chamber Symphony No.2) was detrimental to the performance of rats on a discrimination task 22 . In our studies, we used retrograde Mozart music as a contrast test for Mozart music.…”
Section: Discussionmentioning
confidence: 99%
“…Our concern was whether a music environment is always good? Most of the reports in the literatures have focused on the beneficial effect of music 1 20 , but an early report also suggested that stimulation with non-rhythmic Schoenberg music (Chamber Symphony No.2) was detrimental to the performance of rats on a discrimination task 22 . In our studies, we used retrograde Mozart music as a contrast test for Mozart music.…”
Section: Discussionmentioning
confidence: 99%
“…Some types of music influence rodent social behavior (45) and discrimination performance (46), particularly if timbre cue of music is present (47). Importantly, our results largely confirm that when pulsed tones are used with or without patterns, this effect is not observed (reviewed in 48).…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, some animals take pleasure in moving to the rhythm of music, which seems evident when watching the dancing cockatoo 'Snowball' on youtube.com. Scientific studies of animals (including non-human primates) have, however, consistently failed to show any sort of pleasure or displeasure related to music-like activity or perception (Bates and Horvath, 1971;Hauser and McDermott, 2003;Steele, 2006), although there is recent evidence that music can act in conjunction with other cues as a significant aversive noisy stressor even in rats (Reynolds and Berridge, 2008). While studies of our closest cousins have shown that some of the basic abilities underlying music perception, such as octave recognition, may be in place (Hauser and McDermott, 2003), monkeys are unaffected by dissonance and consonance (McDermott and Hauser, 2004) and do not appear to take pleasure in music overall (McDermott and Hauser, 2007).…”
Section: Introductionmentioning
confidence: 99%